2019 IEEE 26th Symposium on Computer Arithmetic (ARITH) 2019
DOI: 10.1109/arith.2019.00011
|View full text |Cite
|
Sign up to set email alerts
|

Error Bounds for Computer Arithmetics

Abstract: This note summarizes recent progress in error bounds for compound operations performed in some computer arithmetic. Given a general set of real numbers together with some operations satisfying the first standard model, we identify three types A, B, and C of weak sufficient assumptions implying new results and sharper error estimates. Those include linearized error estimates in the number of operations, faithfully rounded and reproducible results. All types of assumptions are satisfied for an IEEE-754 p-digit b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Note that ( 5) is valid for any order of addition in the summation. Recently, it was shown that γ n can be replaced by nu, and the restriction on n can be removed [12,13,14,15]. The algorithm AccSumK is based on the error-free transformations of addition and/or multiplication of two floating-point numbers.…”
Section: Accurate Summation Algorithm Accsumkmentioning
confidence: 99%
“…Note that ( 5) is valid for any order of addition in the summation. Recently, it was shown that γ n can be replaced by nu, and the restriction on n can be removed [12,13,14,15]. The algorithm AccSumK is based on the error-free transformations of addition and/or multiplication of two floating-point numbers.…”
Section: Accurate Summation Algorithm Accsumkmentioning
confidence: 99%
“…is bounded by u/µ(x). This allows one for instance to show that the relative error due to rounding is bounded by u/(1 + u) [4], and to show very tight bounds on the relative errors of Floating-Point operations [3], [6]. We assume that all intermediate calculations are performed in the same format.…”
Section: Rn(x) − X Xmentioning
confidence: 99%
“…We start by computing (a • x) • x: the relative error of that calculation was studied in Section I-B, with bounds given for the various subintervals in Table II. The relative error of the last operation is bounded by u/µ(ax 3 ), i.e., it is given by (6). As previously, we need to order the comparison constants of Table II and ( 6).…”
Section: Computation Of Axmentioning
confidence: 99%
See 2 more Smart Citations